eSports in K-12 and Post-Secondary Schools - Gregory Rothwell; Michael Shaffer (MDPI AG, 2019)
eSports is a rising modality of sports entertainment in the United States and has growing implications for education. Providing competitive eSports teams in schools satisfies the growing desire to train and educate students on the skills emphasized in STEM and Career Technical Education (CTE) education, as well as in programs such as English and Language Arts. eSports develop the soft skills universities and employers like to see in a student graduating from high school. As the market continues to grow for eSports, opportunities for post-secondary education as well as for prospective employment will increase. The popularity of eSports will continue to grow, and this popularity will be reflected in the schools.